Pharmacokinetic and pharmacodynamic properties of canakinumab in patients with gouty arthritis. (30th September 2013) - Chakraborty, Abhijit; Van, Linh M.; Skerjanec, Andrej; Floch, David; Klein, Ulf R.; Krammer, Gerhard; Sunkara, Gangadhar; Howard, Dan
Abstract Pharmacokinetics and pharmacodynamics of the anti‐interleukin (IL)‐1β monoclonal antibody, canakinumab, in gouty arthritis patients from three studies are reported. Canakinumab has low serum clearance (0.214 L/day), low steady‐state volume of distribution (7.44 L), a 25.8‐day half‐life, and approximately 60% subcutaneous absolute bioavailability in a typical 93‐kg patient. Creatinine clearance had a small positive impact on serum canakinumab clearance that is not likely to be clinically relevant. Binding to circulating IL‐1β was demonstrated by increases in total serum IL‐1β following canakinumab dosing. Total IL‐1β kinetics and canakinumab pharmacokinetics were characterized by a population‐based pharmacokinetic‐binding model, where the estimated apparent in vivo dissociation constant (signifying binding affinity of canakinumab to circulating IL‐1β) was 0.99 nmol/L in gouty arthritis patients. Canakinumab treatment provided rapid, sustained decreases in C‐reactive protein and serum amyloid A, provided superior pain relief to triamcinolone acetonide, and increased time to first recurrent attack (P ≤ 0.01 favoring all canakinumab doses vs. triamcinolone acetonide).